The generalized principle of localization for the N-fold Fourier integrals - Ahmedov, Anvarjon (Universiti Putra Malaysia Press, 2010)
In this paper, we investigate the almost everywhere convergence properties of the Riesz means of the eigenfunction expansions (multiple Fourier integrals), associated with Laplace operator. The generalized principle of localization for the Riesz means of the order s = (N-1)(1/p-1/2), 1≤p≤2 is proved.